Aprendizagem da leitura a partir de material multimodal visando à construção de sentido - Inácio, Adriana da Silva Araújo (2016)
This dissertation takes as a starting point the fact that the process of constructing meanings in multimodal texts involves the contribution of verbal and non-verbal codes, which integrate themselves in a collaborative action in order to establish communication. Therefore, explicit/implicit elements add up to the textual composition in meaningful arrangements materializedinto texts (re)createdby the reading subject. It is important to highlight that this process depends on the reader’s repertoire which involves linguistics, discourse and image knowledge. For this reason, we have chosen to develop a group of 9th grade students with whom I work at a public school in Aracaju verbal and visual language literacy aiming to improve their reading competence and reflexive thinking. For the purpose of achieving such scope, we have developed the digital game Na Trilha dos sentidos, directed into building meanings from strips and publicity ads, both multimodal kinds of texts. We have been supported by the social interactionist linguistic theories related to the conception of genre by Marcuschi (2008); we have resorted to Koch (2006, 2015) to debate the concept of resumption by the pronominal anaphora; we have sought the basis for a concept of reading in Kleiman (2000); we have read Cavalcante e Custódio (2010) for the concept of text and Bakhtin/Volochinov (1998 [1929]) for information about the discursive context and dialogism; Kress e Van Leeuwen (1996) have made it possible for us to organize the visual resources studies, among which we stress salience and framing; besides using Fialho’s ideas (2005) for the pedagogic game as an auxiliary resource functionality, a motivation in the learning process. The study followed the principles of the educational actionresearch, defined by Tripp (2005) as a strategy for developing teachers who aim at enhancing their teaching practices and, consequently, their students’ learning. This theoretical input has contributed for the elaboration of the tasks in the game created by researcher. We have observed, from the application and outcomes analysis, that using this pedagogic resource has leaded to students’ involvement with contents, resulting in a broader comprehension of materials in which linguistic, discursive and imagetic aspects have collaborated in the constitution of a single verbal and visual text. We have also noticed the enhancement of the interpretation of meanings from inferences built by means of diverse language resources combined analysis. In spite of its limited reach, as it was restricted to only one group of students, this research suggests that the use of pedagogic practices with multimodal materials based in games should be increased, as it collaborates with the enlargement of the elementary school students’ comprehension ability.